(untitled) (Research, Society and Development, 2022)
The oil industries are considered as the main energy resources, but as producers simultaneously of large amounts of hydrocarbon residues that are discarded in soil and water. Contamination by petroleum and derivatives, including heavy metals, is normally treated through physical, chemical or biological methodologies. Thus, biosurfactants emerge as a promising alternative for the removal of oil and its derivatives due to their amphipathic nature, with hydrophilic and hydrophobic portions allowing these molecules to have the ability to reduce interfacial tension, disperse oil particles, have high surface activity, having low toxicity and high biodegradability, being ecologically correct, in addition to being active under extreme conditions of salinity, pH and temperature. The present study is a narrative review, consisting of a broad analysis of the literature. The aim of this work is to address the potential of microbial biosurfactants to be applied in environmental bioremediation. The searches for the articles used to compose this study were carried out in digital scientific databases, using keywords such as biosurfactants, oil, petroderivatives, bioremediation and heavy metals. This review provides information on the properties of biosurfactants, producing microorganisms, nutritional factors and the application of biosurfactants as a favorable alternative in the removal of oil and derivatives, oil spills, pipeline and heavy metal cleaning.